The Elusive Covenant A Structural-Semiotic Reading of Genesis - Prewitt, Terry J. (Indiana University Press, 1990)
The Elusive Covenant takes a fresh look at the book of Genesis, at the foundational text of the Hebrew bible. Uniting the studies of literary form, sign theory, and kinship structures, Terry J. Prewitt demonstrates the close relationship between the unfolding genealogies and the narrative structures of Genesis. The links between kinship structure and narrative structure, fashioned from diverse written and oral sources, underscore the sense of Genesis as a political document, created by a particular priesthood. The ingenious and informed method of The Elusive Covenant breaks from traditional biblical analysis. Prewitt's "whole-text" perspective and his search for a unified structure in Genesis results in innovative character treatments and a rich appreciation of the scriptural integration of history, social depiction, and spatial representation. At the same time, the author remains cognizant of source-critical and form-critical approaches. Overall, Prewitt's detailed analyses and broad interpretation establish important new connections between Genesis and other biblical scriptures (Exodus, Numbers, Joshua, and so on) and lead to conclusions of broad significance for those in the fields of anthropology, religion, and semiotics.